1977
DOI: 10.1073/pnas.74.8.3602
|View full text |Cite
|
Sign up to set email alerts
|

Conformational requirements for dopamine-induced vasodilation.

Abstract: ABSIRACT The availability of a series of semi-rigid analogs of dopamine and epinine has made it possible to investigate the conformational requirements for action on dopamine and 2-adrenergic vascular receptors. The analogs were screened for dopamine-agonist action by intra-arterial injections into the renal vascular bed and for P2-adrenergic activity by similar injections into the femoral vascular bed in dogs pretreated with phenoxybenzamine. 2-Amino-6,7-dihydroxy-1,2,3,4-tetrahydronaphthalene and its N-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In contrast, 5,6-dihydroxy-2-aminotetralin (5,6-diOH ATN), which holds the dopamine skeleton in its a-rotameric cis extreme was some 120 times less active. A similar preference for the 6,7-dihydroxy analogue has been observed previously in several dopaminergic systems (Volkman et al, 1977;Woodruff et al, 1977). Furthermore, N , N-n-dipropyl-5,6-dihydroxy aminotetralin (N, N-n-dipropyl-5,6-diOH ATN), a potent dopaminergic agonist (Cannon et al, 1978) with an IC,, value of 30 nM, was the most potent agonist tested at displacing stereospecific C3H]spiperone binding in the bovine retina ( Fig.…”
Section: Inhibition Of C3h]spiperone Binding By Drugs Insupporting
confidence: 79%
“…In contrast, 5,6-dihydroxy-2-aminotetralin (5,6-diOH ATN), which holds the dopamine skeleton in its a-rotameric cis extreme was some 120 times less active. A similar preference for the 6,7-dihydroxy analogue has been observed previously in several dopaminergic systems (Volkman et al, 1977;Woodruff et al, 1977). Furthermore, N , N-n-dipropyl-5,6-dihydroxy aminotetralin (N, N-n-dipropyl-5,6-diOH ATN), a potent dopaminergic agonist (Cannon et al, 1978) with an IC,, value of 30 nM, was the most potent agonist tested at displacing stereospecific C3H]spiperone binding in the bovine retina ( Fig.…”
Section: Inhibition Of C3h]spiperone Binding By Drugs Insupporting
confidence: 79%
“…Structural analogs of clonidine, such as St-91 (113) and SK&F 35886 (114), although potent a2-adrenoceptor agonists in vitro, do not produce clonidine-like stimulation of central tt2-adrenoceptor in the intact animal. AGN 190851 ( 115) is an analog of UK 14,304 in which the (114) SK&F 35886 (R = CH3) (115) AGN 190851 heterocyclic ring is saturated.65,66 This modification dramatically changes the partition coefficient between octanol and neutral phosphate buffer,66 presumably as a consequence of increasing the basicity of the molecule. AGN 190851 is a potent a2-adrenoceptor agonist in several in vitro assays, such as inhibition of adrenergic neurotransmission in the guinea pig atrium or contraction of canine saphenous vein.…”
Section: N-ch3mentioning
confidence: 99%
“…There is also one interesting fact concerning the different modes of action of 5,6-dihydroxy-2-aminotetralin and 6,7-dihydroxy-2-aminotetralin that could imply two types of dopamine receptors. Volkman et al (1977) demonstrated that the 6,7-dihydroxylated compound is more potent than the 5,6-dihydroxylated in inducing renal vasodilation in dogs (a D-i receptor effect, according to Kebabian & Calne). Inversely, Costall et al (1977) found the 5,6dihydroxy derivative to be considerably more potent in inducing stereotyped behaviour after direct injection into the nucleus accumbens of rat brain, assumedly a D-2 receptor effect.…”
Section: (G) Multiple Dopamine Receptorsmentioning
confidence: 99%